Single-Walled Carbon Nanotubes Alter Cytochrome C Electron Transfer and Modulate Mitochondrial Function - Ma, Xiaowei (2012)
Single-walled carbon nanotubes (SWCNTs) are broadly used for various biomedical applications such as drug delivery, in vivo imaging and cancer photothermal therapy due to their unique physiochemical properties. However, once they enter the cells, the effects of SWCNTs to the intracellular organelles and macromolecules are not comprehensively understood. Cytochrome c (Cyt c), as a key component of the electron transport chain in mitochondria, plays an essential role in cellular energy consumption, growth and differentiation. In this study, we found the mitochondrial membrane potential (MMP) and mitochondrial oxygen uptake were greatly decreased in human epithelial KB cells treated with SWCNTs, which accompanies the reduction of Cyt c. SWCNTs deoxidized Cyt c in a pH dependent manner as evidenced by the appearance of a 550 nm characteristic absorption peak, which intensity increased as pH increase. Circular dichroism measurement confirmed the pH-dependent conformational change, which facilitated closer association of SWCNTs with the heme pocket of Cyt c and thus expedited the reduction of Cyt c. The electron transfer of Cyt c is also disturbed by SWCNTs, as measured with electron spin resonance spectroscopy. In conclusion, the redox activity of Cyt c was affected by SWCNTs treatment due to attenuated electron transfer and conformational change of Cyt c, which consequently changed mitochondrial respiration of SWCNTs treated cells. This work is significant to SWCNTs research because it provided novel understanding to the disruption of SWCNTs to the mitochondria and has important implications for biomedical applications of SWCNTs.